Research in organizational change and development. Vol. 25 - Shani, Abraham B. Rami; Noumair, Debra Ann (Emerald Publishing Limited, 2017)
2017 marks the silver anniversary of the Research in Organizational Change and Development series, founded in 1987 by Dick Woodman and Bill Pasmore, and currently edited by Rami Shani and Debra Noumair. This volume includes contributions from authors who have published in the first few volumes, contributions that examine the impact of the research published in the series on OD&C research, theoretical developments and practice. Highlights include contributions from Bill Pasmore and Dick Woodman as well as David Coghlan that focus on the essence and impact of the research reported in the last 24 volumes and possible research trajectories; Philip Mirvis and Mitchell Marks- the second recipients of the Pasmore-Woodman award (AOM 2016) on the highs and lows of co-researching; David Cooperrider on the evolution of Appreciative Inquiry since the foundation manuscript was published in ROCD Volume 1 (1987); Todd Jick & Kinthi Sturtevant who take stock of 30 years of change management, asking questions of and about its future and; Marvin Weisbord́s reflection on forty years of being a scholarly-practitioner in the field.
Prelims -- The future of research and practice in organizational change and development -- Taking stock of 30 years of change management: is it time for a reboot? -- The gift of new eyes: personal reflections after 30 years of appreciative inquiry in organizational life -- How organizational transformation has been continuously changing and not changing -- Co-researching and doing m&a integration: crossing the scholar-practitioner divide -- X-ray vision at work: seeing inside organizational life -- Achieving strategic change through performance management: the role of identity threat -- Organizational change and ambidexterity in higher education: a case study of institutional merger -- Learning to fly and other life lessons -- How might we learn about the philosophy of odc research from 24 volumes of rocd? an invitation to interiority -- About the contributors.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Organizational change; Business & Economics -- International -- General; Organizational theory & behaviour